Characteristics and mechanism of large deformation of a reservoir colluvial landslide-a case study of the Yulinerzu landslide in Xiluodu Reservoir, China - Wei, Jinbing; Wang, Dikai; Yang, Zhongkang; Wang, Jiexiong; Li, Yuming; Hu, Wanyu (Frontiers in Earth Science, 2024)
The reactivation of colluvial landslides in reservoir banks poses a serious threat to the safety of hydropower projects and nearby towns. This study aimed to research the morphological evolution of this type of landslides under the action of reservoir water and its impact on landslide stability., The study focuseding on the Yulinerzu landslide, a large reactivated colluvial landslide in the Xiluodu Reservoir. Field surveys were conducted to analyze the geological structure of the landslide. In situ monitoring and surveys were used to obtain the deformation characteristics and morphological evolution of the landslide. A combined seepage-slope stability analysis was conducted to reveal the deformation mechanism. The results show that the reactivation of the Yulinerzu landslide is dominated by reservoir water fluctuations rather than rainfall. The underlying geological condition of the colluvial landslide is its hydrogeological structure, which causes the landslide to deform in a steplike manner during reservoir operation. With the accumulation of displacement and morphology evolution, the landslide shows displayed self-stabilizing characteristics. Therefore, the evolution of landslide morphology needs to be considered in the stability analysis and risk assessment of large deformation landslides.